2002
DOI: 10.1021/jf020527q
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Defensin Encoded by a Mungbean cDNA Exhibits Insecticidal Activity against Bruchid

Abstract: A cDNA encoding a small cysteine-rich protein designated VrCRP was isolated from a bruchid-resistant mungbean. VrCRP encodes a protein of 73 amino acids containing a 27 amino acid signal peptide and 8 cysteines. On the basis of the amino acid sequence similarity and conserved residues, it is suggested that VrCRP is a member of the plant defensin family. VrCRP protein was obtained by overexpression of VrCRP with a truncated signal peptide in an IMPACT system. Artificial seeds containing 0.2% (w/w) of the purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 38 publications
2
78
0
Order By: Relevance
“…Defensin expression in plants can typically be found in leaves (Terras et al, 1995), seeds (Almeida et al, 2000;Chen et al, 2002), flowers (Park et al, 2002;Lay et al, 2003) and can be induced by stress (Koike et al, 2002) or pathogen inoculation (Manners et al, 1998;Berrocal-Lobo et al, 2002). Plant defensins have been identified that confer resistance to fungal (Gao et al, 2000;Park et al, 2002;Cabral et al, 2003), bacterial (Koike et al, 2002), or insect pathogens (Chen et al, 2002;Lay et al, 2003).…”
Section: A Diverse Family Of Cys Cluster Proteins With Similarity To mentioning
confidence: 99%
“…Defensin expression in plants can typically be found in leaves (Terras et al, 1995), seeds (Almeida et al, 2000;Chen et al, 2002), flowers (Park et al, 2002;Lay et al, 2003) and can be induced by stress (Koike et al, 2002) or pathogen inoculation (Manners et al, 1998;Berrocal-Lobo et al, 2002). Plant defensins have been identified that confer resistance to fungal (Gao et al, 2000;Park et al, 2002;Cabral et al, 2003), bacterial (Koike et al, 2002), or insect pathogens (Chen et al, 2002;Lay et al, 2003).…”
Section: A Diverse Family Of Cys Cluster Proteins With Similarity To mentioning
confidence: 99%
“…They have been identified in diverse taxa with many defense roles, including antifungal (Gao et al, 2000;Park et al, 2002;Cabral et al, 2003;Lay et al, 2003a), antibacterial (Osborn et al, 1995;Segura et al, 1998;Koike et al, 2002), anti-insect (Chen et al, 2002;Lay et al, 2003b), and protease inhibitory (Osborn et al, 1995;Wijaya et al, 2000) activities. In many cases, small differences in amino acid sequence can predict the specificity of the defense role (GarciaOlmedo et al, 1998).…”
mentioning
confidence: 99%
“…The deduced nucleotide sequence of the defensin gene showed more than 90% identity to the nucleotide sequence of the well characterized defensins of Vigna radiata . A bacterially expressed mungbean ( Vigna radiata ) defensin have been earlier reported (VrCRP) to have exhibited both antifungal and insecticidal activities [40, 41]. Plant defensin from cowpea have been shown to be efficiently inhibiting α- amylases from bean weevils and Mexican bean weevil [42].…”
Section: Discussionmentioning
confidence: 99%